DETERMINAN PRICE EARNING RATIO SAHAM YANG TERDAFTAR DALAM JAKARTA ISLAMIC INDEX (JII) PERIODE 2011 – 2017. - Aysha Dhamaring Nugroho; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
It is very important for investor to be able to assess whether a stock will be able to provide a high return of investment in the future. There are various kinds of approaches that can be used by investor to assess the performance of a stock in the stock market, two of which are technical analysis and fundamental analysis. Price earning ratio is part of ratio that are used in fundamental analysis and price earning ration is often used by investor as a refrence to read the performance of a stock in the future. This study are focusing on finding which variabel can affect the value of price earning ratio of a stock, using VECM method this study finds that debt to equity ratio, return on equity, dividend payout ratio and current ratio in long -run affecting price earning ratio in a significant way.Keywords: financial ratio, price earning ratio, fundamental analysis, Indonesia syariah stock market